Platelet Dysfunction in Cardiac Surgery: When is the Best Time to Assess It? An Observational Single Center Study. (March 2022) - Auci, Elisabetta; Vendramin, Igor; Barbariol, Federico; Riccardi, Ilaria; Gigante, Andrea; Baroselli, Antonio; Bove, Tiziana; Bassi, Flavio; Vetrugno, Luigi; Livi, Ugolino
Purpose. Cardiac surgery is characterized by a high risk of complications related to perioperative bleeding. Guidelines suggest the use of local algorithms based on perioperative point-of-care tests to assess and manage potential coagulation abnormalities. We investigated whether heparin reversal administration affects the adenosine-5-diphosphate (ADP) test values, thus identifying the earliest time point following cardio-pulmonary bypass that permits the promptest detection and treatment of potential platelet dysfunctions. Methods. This was a retrospective, single-center, observational study enrolling cardiac surgery patients requiring cardiac bypass. ADP-tests at 4 different time-points during surgery (T0: baseline, T1: at aortic de-clamping, T2: 10 minutes after protamine administration, and T3: at the end of surgery) were performed. Results. 63 patients undergoing elective cardiac surgery were studied. Baseline ADP-test values were almost constantly greater than intraoperative values, and end of surgery values were often greater than previous intraoperative values. The only difference that proved to be not statistically significant was between T1 and T2, with a clinically insignificant mean difference of −.2 U (95%CI of difference: −6.9 - 6.5 U). There was no correlation between the variation in ADP-test values pre- and post-protamine administration and the protamine-to-heparin ratio. Conclusion. The results of the present study support the hypothesis that the ADP-test could be performed early, at aortic de-clamping before protamine administration. This approach allows for the promptest assessment of a potential impairment in platelet function, and its timely correction.